Applications of indicators as a strategy for the management of the use and cost of antimicrobials in a university hospital (Research, Society and Development, 2021)
The increase in the consumption of antimicrobials has resulted in high costs for public health, in addition to impacting the increase in microbial resistance as a worldwide problem. This study aimed to assess the consumption and economic impact of antimicrobials in a University Hospital, through the analysis of use and costs, in the period from 2015 to 2017. It is a longitudinal, analytical study with retrospective data collection. Their consumption was calculated using the indicators recommended by the World Health Organization and finally, the cost of consumption of antimicrobials was analyzed using the unit values in reais (R $). For the statistical analysis, the t test and statistical significance were used with a 95% confidence interval. By calculating the defined daily dose, the results showed a decrease in consumption in the first year, followed by an increase in consumption between years, especially the classes of carbapenems, penicillins, cephalosporins and glycopeptides. Meanwhile, the measured treatment time decreased during the study period. With regard to cost, there was a reduction between 2015 and 2016 and shortly after an increase between 2016 and 2017. It is concluded that the methods of consumption analysis are tools that guide the management of the rational use of antimicrobials and contribute to the decrease in costs in the hospital environment.